(untitled) (Conferencea, 2022)
Special terminology on artificial intelligence and intelligent systems began to form in the 60s of the twentieth century. The first stage of terminology formation is always distinguished by the presence of many synonymous terms that are used by various schools and groups of specialists. At this stage, terms quickly appear and some of them also quickly disappear. By the mid-70s, the terminology in the field of artificial intelligence began to be established. There are terms that are recognized by the vast majority of experts. All these terms (with rare exceptions) are English in origin, since it was in the USA that intensive research was carried out in this area. Finally, the basic terminology was fixed in the first half of the 80s. From this period, dictionaries and encyclopedic reference books on artificial intelligence began to be published.